دور الفيسبوك في تنمية الثقافة الصحية - محمد بن عون; الزوبير بن عون (جامعة عمار ثليجي الاغواط, 2024)
- ملخص: نهدف من خلال هذه الدراسة الى معرفة دور الفيسبوك في تنمية الثقافة الصحية لدى مستخدميه، واعتقدنا بأن تنمية الثقافة الصحية راجعة لكيفيات استخدام الموضع وإلى اهتمامات وتفاعل المستخدمين مع المنشورات المتعلقة بقضايا الصحة والمرض. وفي سبيل ذلك اعتمدنا على استراتيجية منهجية متمثلة في استخدام المنهج الوصفي، وأداة الملاحظة، المقابلة والاستبيان الالكتروني في جمع المعلومات عن عينة متكونة من 66 مفردة. وبعد عرض وتحليل البيانات خلصنا الى نتيجة عامة مفادها أن موقع التواصل الاجتماعي الفيسبوك يؤدي بالفعل أدوار ووظائف إيجابية للمستخدمين له من افراد العينة، بحيث يساهم مساهمة كبيرة في تنمية الثقافة الصحية ويرجع ذلك بالطبع الى كيفيات الاستخدام واهتمامات المبحوثين فيما يتعلق بمتابعة ومشاركة المنشورات المتعلقة بالصحة والمرض. - الكلمات المفتاحية: مواقع التواصل الاجتماعي، الفيسبوك، الثقافة الصحية. Abstract: Through this study, we aim to know the role of Facebook in developing health culture among its users, and we believe that developing health culture is due to how the site is used and to users’ interests and interaction with publications related to health and disease issues. In order to do this, we relied on a methodological strategy represented by the use of a descriptive approach, observation tools, interviews, and an electronic questionnaire to collect information about a sample consisting of 66 individuals. After presenting and analyzing the data, we concluded with a general conclusion that the social networking site Facebook actually performs positive roles and functions for its users among the sample, so that it contributes significantly to the development of health culture. This is of course due to the methods of use and the interests of the respondents with regard to following and sharing publications related to health and disease. - key words: Social networking sites, Facebook, health culture.
دراسة ميدانية لعينة من مستخدمي التواصل الاجتماعي